Degradation of biodegradable bioplastics under thermophilic anaerobic digestion: A full-scale approach. (25th September 2022) - Cucina, Mirko; Carlet, Lara; De Nisi, Patrizia; Somensi, Cleder Alexandre; Giordano, Andrea; Adani, Fabrizio
Abstract: Anaerobic digestion of bioplastics' wastes may represent a valuable disposal strategy for these important substitutes for plastics, in order to reduce their leakage into the environment and to produce bioenergy in the form of biomethane, contributing positively to the sustainability of the entire bioplastics' life chain. Only lab-scale data about bioplastics' anaerobic degradability and biomethane production have been produced until now, using approaches far from full-scale conditions. This paper presents a novel approach in studying the potential of bioplastics to produce biomethane because a pioneering methodology was adopted, allowing acquisition of full-scale data that can be useful to further attest environmental and economic sustainability in recovering bioplastics' wastes. A simple and replicable experimental approach was proposed to studying bioplastic degradability during anaerobic digestion, which consisted of placing the bioplastics into a full-scale digester within perforated steel boxes. Three different bioplastics items (one starch-based and two polylactic-acid based) were co-digested with organic wastes in a real anaerobic digestion plant using the real process parameters (thermophilic temperature for 30 days of hydraulic retention time followed by 30 days of mesophilic maturation). The experiments were replicated at laboratory-scale to evaluate the potential for biomethane recovery from bioplastics degradation. Laboratory-scale data did not differ from the data coming from the full-scale experiment, i.e., bioplastic degradation was not affected by the reactor volume. Bioplastics showed an average degradation of 27 ± 5% on a weight basis and a different degradation mechanism for the two types studied was found through Fourier Transform-InfraRed spectroscopy (FTIR) analysis. Starch-based bioplastics showed a quick consumption of the starch component, followed by a slow degradation of the polyester fraction. Polylactic acid bioplastics were degraded without chemical changes to their composition. In both laboratory-scale and full-scale experiments, temperature was a key parameter affecting bioplastics' degradation, i.e., thermophilic temperatures were needed to obtain a significant degradation. Biomethane potential determination of the bioplastics (135 ± 23 NLCH4 kg Volatile Solids −1 as average at the end of the thermophilic digestion) proved that anaerobic digestion of bioplastics may be a sustainable approach, reducing bioplastic leakage and producing bioenergy (biogas), respecting Circular Economy principles. Anaerobic digestion may represent a valorisation treatment for bioplastics' wastes contributing positively to the sustainability of the entire bioplastics' life chain. Graphical abstract: Image 1 Highlights: First assessment of bioplastics' anaerobic degradation using a full-scale approach. Starch-based and polylactic acid-based bioplastics degrade differently during AD. Bioplastics' anaerobic degradation may enhance biomethane production from AD plant. AD of bioplastics can avoid their leakage into natural environments.